Religious Coping Among Muslim University Students: Psychometric Evaluation of The Brief RCOPE-Malay - Ahmad Sabki, Zuraida; Sa’ari, Che Zarrina; Syed Mohammad Hilmi b Syed Abdul Rahman; Che Nordin, Mohd Khairul Naim; Muhamad, Asmawati (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Religious coping is an important dimension of psychological adjustment, particularly in Muslim populations where faith is central to managing stress. The Brief Religious Coping Scale (Brief RCOPE) is widely used to assess positive (PRC) and negative (NRC) religious coping; however, a validated Malay-language version has not been available. The study aimed to assess the psychometric properties of the Malay Brief RCOPE (Brief RCOPE-M) among Muslim students in a Foundation in Islamic Studies program at a Malaysian public university. A total of 144 Malay Muslim students (mean age = 18.56±0.50, 72.9% female) participated. The Brief RCOPE underwent forward–backward translation and cultural review. Exploratory factor analysis (principal axis factoring, oblimin rotation) examined factor structure. Reliability was assessed with Cronbach’s alpha, and convergent validity was evaluated through correlations with the Malay versions of the Duke University Religion Index (DUREL-M), Copenhagen Burnout Inventory (CBI-M), and Brief Resilience Scale (BRS-M). Findings supported a two-factor solution consistent with PRC and NRC, with eigenvalues > 1, explaining 61% of the variance. Internal consistency was high (PRC α = 0.93; NRC α = 0.82). PRC was positively correlated to religiosity and resilience, while NRC was positively correlated to burnout and negatively to resilience, supporting convergent and concurrent validity. PRC and NRC were weakly correlated (r = – 0.12), suggesting relative independence. No gender differences between male and female students for PRC and NRC. Overall, the Brief RCOPE-M demonstrated sound psychometric properties and provides a reliable and valid instrument for assessing religious coping among Malay-speaking Muslim populations in Malaysia. Future studies should apply confirmatory factor analysis (CFA) and cultural validation to ensure a robust and contextually appropriate instrument.